Terrestrial Nocturnal Roosting Behavior of Black‐necked Cranes (Grus nigricollis) on the Yunnan‐Guizhou Plateau: Active Choice or Forced Environmental Adaptation - Xinlei Hou; Guangyi Lu; Shuxia Zhang; Liping Feng; Guopeng Ren; Heqi Wu (Ecology and Evolution)
ABSTRACT Nocturnal roosting sites are integral to bird habitats, with their use and selection by birds serving as indicators of behavioral adaptations to environmental pressures. Black‐necked Cranes (Grus nigricollis), which typically roost in shallow water, have exhibited an unexpected “terrestrialization” of nocturnal roosting sites within their eastern wintering population of southwest China. Despite this phenomenon being documented since the late 20th century, research on terrestrial nocturnal roosting behavior remains limited, hindered by technological challenges. To address this knowledge gap, we combined GPS‐GSM tracking data from 14 individuals monitored between 2015 and 2022 in northeastern Yunnan and western Guizhou with remote sensing imagery to systematically analyze their nocturnal roosting patterns. Our results indicated that area of water body, the location of foraging grounds, and individual behaviors influenced the proportion of terrestrial nocturnal roosting in Black‐necked Cranes. On land, Black‐necked Cranes preferred to roost on highlands (headwaters, uphill terraces, mountain tops, and local ridges) and avoided valleys (canyons, shallow valleys, and U‐shaped valleys). Notably, nocturnal terrestrial roosting sites were associated with increased nocturnal mobility compared to shallow water (11.6% vs. 0.8%). These findings suggest that terrestrial roosting behavior may reflect adaptive trade‐offs under habitat pressure. We recommend that regional conservation strategies should prioritize the following: (1) Protect existing large wetlands, (2) Connect and restore fragmented small wetlands, (3) Strengthen nighttime monitoring of the Black‐necked Crane, and (4) Strictly manage free‐ranging dogs to minimize anthropogenic disturbance on terrestrially roosting cranes.